Desarrollo de api Gateway para el sistema de proyectos de investigación de la UNACH basado en microservicios - Nuñez Paguay, Jacqueline Elizabeth (2024)
The main problem addressed by this project is the need for specialized technological infrastructure at UNACH. Currently, technological barriers limit the efficiency of research management. The design and development of an API Gateway is proposed as a strategic solution to optimize the integration of microservices, overcoming these barriers and enhancing the institution's research capabilities. Implementing this project not only improves efficiency in research management but also strengthens the university's position as a leader in the convergence of technology and scientific knowledge. The justification for this project lies in the need to adopt modern technologies that facilitate data management and optimize collaboration among researchers. The microservices structure, supported by an API Gateway, allows for greater flexibility and adaptability to technological changes and the demands of academic research. This advanced technological approach not only enhances the current infrastructure but also lays the foundation for future innovations and developments at the university. The technical implementation of the API Gateway includes defining controllers that handle HTTP requests (GET, POST, PUT, DELETE) and call the corresponding services in the business logic layer, responding in formats such as JSON or XML. This structure facilitates data management and processing, ensuring efficient communication between the different microservices and the clients interacting with the system. The project also included a thorough performance evaluation of the module using tools such as Blazer Meter. Load tests were conducted with multiple concurrent users to identify and resolve performance issues, ensuring that the system can effectively handle the demands of real-world usage. The results of these tests were thoroughly analyzed and presented in statistical graphs, providing a clear understanding of the system's behavior under different load conditions.